The Impact of Marijuana Legalization on Police in Colorado - Iannacchione, Brian (Criminal justice review, 2023)
The purpose of this study was to survey a random sample of police departments in Colorado to assess their views on the impact of marijuana legalization in the state. While police perceptions have been used in prior research to assess other topics, very few studies have assessed police perceptions of marijuana legalization. To address this, police officers and sheriff deputies at 64 randomly selected police departments across Colorado were administered surveys that assessed the impact marijuana has had on enforcement and their personal perceptions of marijuana. In addition, qualitative questions were asked to explore these topics in greater detail. The findings of the 131 respondents suggest that most police officers in Colorado are slightly supportive of legalization, but have noted that it has made their job more difficult.